NEW APPROACHES TO UNDERSTANDING NATIONAL-PATRIOTIC EDUCATION OF YOUTH - Тімкін, І. Ф.; Новікова, Н. Є. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the article approaches to understanding national – patriotic education of the youth of today as a system of measures aimed at building a «new» Ukrainian acting on the basis of national and European values